2019
DOI: 10.1111/psyp.13342
|View full text |Cite
|
Sign up to set email alerts
|

Blunted neural response to gains versus losses associated with both risk‐prone and risk‐averse behavior in a clinically diverse sample

Abstract: Reduced responsiveness to reward has been associated with both risk‐prone and risk‐averse behavior, common features of externalizing and internalizing psychopathology, respectively. Thus, evidence has suggested a potential quadratic relationship (i.e., inverted U) between reward sensitivity and risk‐taking propensity. Blunted response to reward compared to loss may therefore demonstrate transdiagnostic utility as it relates to different patterns of maladaptive risk behavior. The current study sought to disenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 78 publications
(132 reference statements)
0
10
0
Order By: Relevance
“…This component was equally explored in patients suffering from alcohol use disorder vs. controls, but group difference fell short of significance [ 49 ]. Finally, in a clinically diverse sample (depression, substance- and alcohol-use disorder), during another uncertain decision-making task, it has been observed that women displayed larger RewP amplitudes than men, and that a blunted response was related to both extremes of high and low risk proneness, even after controlling for psychiatric diagnosis [ 25 ]. However, our results did not point towards any relation of the RewP with impulsive dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This component was equally explored in patients suffering from alcohol use disorder vs. controls, but group difference fell short of significance [ 49 ]. Finally, in a clinically diverse sample (depression, substance- and alcohol-use disorder), during another uncertain decision-making task, it has been observed that women displayed larger RewP amplitudes than men, and that a blunted response was related to both extremes of high and low risk proneness, even after controlling for psychiatric diagnosis [ 25 ]. However, our results did not point towards any relation of the RewP with impulsive dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another feedback processing component, reward-related positivity (RewP), is believed to index individual differences in relation to reward sensitivity [ 24 ]. A blunted RewP activity has been linked to maladaptive risk-taking behavior, involving both risk aversion and risk proneness [ 25 ]. However, the electrophysiological studies of risk taking during the BART have not explored the relationship with other dimensions of impulsive-related behavior.…”
Section: Introductionmentioning
confidence: 99%
“…And indeed, there is evidence that a more robust neural response to rewards, indicative of greater estimation of their value, is related to greater motivation to act on those rewards (Bakker et al., 2018; Cooper et al., 2017; Genevsky et al., 2017; King‐Casas et al., 2005; Tamir & Hughes, 2018). A modest literature also links the RewP to reward‐related behaviors: For instance, a larger RewP is related to greater reward‐driven response bias (Bress & Hajcak, 2013), more adaptive behavioral strategies in monetary risk tasks (Huggins et al., 2019), better trial‐by‐trial learning (Williams et al., 2019), and greater reported liking of desired rewards (Angus et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, less risk-taking was associated with earning fewer points in the task. Because 64 was communicated to the participants as the most advantageous choice over the whole task, results from our sample may better reflect how reward sensitivity relates to risk-aversion ( Huggins et al, 2019 ) as opposed to heightened propensity for risk.…”
Section: Discussionmentioning
confidence: 99%
“…While overly high reward sensitivity and risk-taking may have consequences for externalizing disorders, blunted reward sensitivity and low risk-taking may have consequences for internalizing disorders ( Bjork and Pardini, 2015 ; Goff et al, 2013 ; Huggins et al, 2019 ; Telzer et al, 2013 ). Therefore, another important future direction is to examine neural reward sensitivity and risk-taking in both healthy subjects and subjects with a range of internalizing and externalizing psychopathology.…”
Section: Discussionmentioning
confidence: 99%